Formulation of microspheres containing Crataegus monogyna Jacq. extract with free radical scavenging activity. (1st February 2014) - Lucconi, Giulia; Chlapanidas, Theodora; Martino, Emanuela; Gaggeri, Raffaella; Perteghella, Sara; Rossi, Daniela; Faragò, Silvio; Vigo, Daniele; Faustini, Massimo; Collina, Simona; Torre, Maria Luisa
Abstract: Extracts of Crataegus monogyna Jacq. (hawthorn) show an interesting free radical scavenging (FRS) effect, related to their flavonoids content. Unfortunately, their oral administration is affected by their low bioavailability. The aim of this work is to obtain a multiparticulate drug delivery system for hawthorn extracts for oral administration. The extracts from flowering tops (FL) or fruits (FR) of hawthorn were obtained with maceration, using ethanol as an extraction solvent, and their antioxidant activity was evaluated. FL extract showed the highest FRS activity (EC50 3.72 ± 1.21 µg/ml), so it was selected to prepare microparticulate systems by a spray-drying technique, which were characterized by granulometric analysis, scanning electron microscopy–energy dispersive X-ray spectroscopy, confocal fluorescence microscopy and hyperoside content. Antioxidant activity was evaluated before and after gastrointestinal transit in vitro simulation. Results indicate that the microparticulate systems maintained the antioxidant activity of hawthorn also after gastrointestinal transit in vitro simulation, exhibiting properties suitable for oral administration.